2004
DOI: 10.1038/sj.hdy.6800589
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships between diploid and allotetraploid cherry species (Prunus avium, Prunus × gondouinii and Prunus cerasus)

Abstract: Prunus avium L. (diploid, AA, 2n ¼ 2x ¼ 16), Prunus cerasus L. (allotetraploïd, AAFF, 2n ¼ 4x ¼ 32) species, and their hybrid Prunus  gondouinii Rehd., constitute the most widely cultivated cherry tree species. P. cerasus is supposed to be an hybrid species produced by the union of unreduced P. avium gametes and normal P. fruticosa gametes. A continuum of morphological traits between these three species makes their assignation difficult. The aim of this paper is to study the genetic relationships between tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 29 publications
1
23
0
2
Order By: Relevance
“…In this study we used two types of molecular markers, microsatellite markers in order to identify sour cherry genotypes (KAÇAR et al 2006, ANTONIUS et al 2012) and AFLP markers in order to identify genotypes within the cultivar Obla~inska (ZHOU et al 2002, TAVAUD et al 2004. A significant correlation (r =0.878), almost identical to the correlation (r = 0.873) obtained by KRICHEN et al (2010) Tab.…”
Section: Discussionsupporting
confidence: 58%
“…In this study we used two types of molecular markers, microsatellite markers in order to identify sour cherry genotypes (KAÇAR et al 2006, ANTONIUS et al 2012) and AFLP markers in order to identify genotypes within the cultivar Obla~inska (ZHOU et al 2002, TAVAUD et al 2004. A significant correlation (r =0.878), almost identical to the correlation (r = 0.873) obtained by KRICHEN et al (2010) Tab.…”
Section: Discussionsupporting
confidence: 58%
“…(Faust and Suranyi, 1997;Saunier and Claverie, 2001). Tavaud et al (2004) also identified 12 cultivars of P. × gondouinii Rehd. which exhibited tree and fruit characteristics that were intermediate between sweet and sour cherry.…”
Section: Duke Cherry Cultivarsmentioning
confidence: 99%
“…Several morphological characterization studies have been carried on the Cerasus species and important results have been obtained, such as on sweet cherry (Christensen 1970), ground cherry , sour cherry (Krahl et al 1991;Rodrigues et al 2008;Rakonjac et al 2010), duke cherry (Tavaud et al 2004), mahaleb (Ganji Moghadam and Khalighi 2007) and some Cerasus genotypes (Shahi-Gharahlar et al 2010).…”
mentioning
confidence: 97%